In Situ : um projecto de trabalho com a comunidade para a conservação do património da Faculdade de Belas-Artes da Universidade de Lisboa - Bento, Beatriz, 1992- (2016)
This master thesis presents an educational project in the heritage field, to perform at the Faculty of Fine Arts of the University of Lisbon with the community that characterizes the place. Descendant of the Academy of Fine Arts, founded and established at the Convent of Saint Francis since 1836, the Faculty of Fine Arts inherited a vast, diverse and very important heritage to understand the progress of both artistic education and practice in Portugal for almost 180 years. To enrich and strengthen the value of our ongoing heritage development (Painting, Sculpture, old Engraving and Drawing), we have been gathering more contemporary artefacts to enrich the original collections and create new modernized collections, such as Multimedia or photography. However, despite all the efforts that have been carried out to conserve and promote the heritage, it’s still notable the lack of communication between the objects and the majority of the community. The artefacts stored in their collections remain unknown to the public, while the artefacts exhibited in the Faculty suffers the harmful consequences, of the recklessness of ignorance and the ephemeral quality that is given to the heritage goods by the community, because of their functional utility in the study of drawing and sculpture. After studying carefully this issue and analysing the actions recently accomplish in the conservation of the Faculty heritage, we proposed a number of innovative activities and interventions to promote dialogue, knowledge and conservation inside of the material and human institution The project that structures and presents this dynamics is called In Situ, and it participates in the development of a more embracing project known by: CAREFUL - implementation of a preventive conservation plan for the collection of the Faculty of Fine Arts, University of Lisbon, created by Faculty of Fine Arts professors Alice Alves, Luísa Arruda and Marta Frade and PHD student Carlos Alcobia